Muscle weakness, health status and frequency of exacerbations in chronic obstructive pulmonary disease. Issue 1041 (2nd March 2012) - Ansari, Khalid; Keaney, Niall; Taylor, Ian; Burns, Graham; Farrow, Malcolm
Abstract : Background: Multiple factors contribute to muscle weakness and reduced muscle mass in chronic obstructive pulmonary disease (COPD) and this impacts patients' quality of life. One factor implicated in this process is systemic inflammation, an accompaniment of acute exacerbations. Recurrent exacerbations are associated with lower health status. This study examines the relationship between muscle weaknesses, health status and exacerbation frequency in a cohort of patients with COPD. Methods: This is an observational study of 188 (95 female) patients with COPD attending two hospital clinics in the northeast of England between 2004 and 2007. We measured spirometry, body mass index, health status (St George's Respiratory Questionnaire) and grip strength and recorded Medical Research Council dyspnoea scores and the frequency of exacerbations in the previous year. Results: Patients were aged 72.5±8.3 years (data expressed as mean±SD) with Medical Research Council score of 3.6±0.8, forced expiratory volume in one second (FEV1 ) of 49.2±21.5 per cent predicted and a total St George's Respiratory Questionnaire score of 72.2±15.5. Grip strength, expressed as per cent predicted, was 72.0±21.8 in men and 81.0±18.2 in women. Exacerbations ranged from zero to five in the previous year and there were associations of reduced grip strength with exacerbation frequency (χ 2 =9.634; p=0.0019) and lower health status (χ 2 =34.00; p<0.001). Conclusion: Our data clearly demonstrate that reduction in grip strength occurs more frequently and to a greater extent in patients with a history of frequent exacerbations and is associated with reduced health status.